Circularly permuted monomeric red fluorescent proteins with new termini in the beta-sheet - Carlson, Haley; Cotton, Darrel W.; Campbell, Robert E. (My University, 2010)
Circularly permuted fluorescent proteins (FPs) have a growing number of uses in live cell fluorescence biosensing applications. Most notably, they enable the construction of single fluorescent protein‐based biosensors for Ca2+ and other analytes of interest. Circularly permuted FPs are also of great utility in the optimization of fluorescence resonance energy transfer (FRET)‐based biosensors by providing a means for varying the critical dipole–dipole orientation. We have previously reported on our efforts to create circularly permuted variants of a monomeric red FP (RFP) known as mCherry. In our previous work, we had identified six distinct locations within mCherry that tolerated the insertion of a short peptide sequence. Creation of circularly permuted variants with new termini at the locations corresponding to the sites of insertion led to the discovery of three permuted variants that retained no more than 18% of the brightness of mCherry. We now report the extensive directed evolution of the variant with new termini at position 193 of the protein sequence for improved fluorescent brightness. The resulting variant, known as cp193g7, has 61% of the intrinsic brightness of mCherry and was found to be highly tolerant of circular permutation at other locations within the sequence. We have exploited this property to engineer an expanded series of circularly permuted variants with new termini located along the length of the 10th β‐strand of mCherry. These new variants may ultimately prove useful for the creation of single FP‐based Ca2+ biosensors.
Circularly permuted monomeric red fluorescent proteins with new termini in the beta-sheet